Consensus views on advance care planning for dementia: a Delphi study. (11th February 2015) - Sinclair, James B.; Oyebode, Jan R.; Owens, R. Glynn
Abstract: The uptake of advance care planning (ACP) is particularly low among people with dementia. This may reflect barriers to communication between professionals, patients and families in the face of lack of consensus about the process. This study aimed to methodically investigate consensus views of how ACP should be explained and carried out with people with dementia. A three‐round Delphi study explored views of how and when ACP should be addressed, what should be covered, who should be involved and why rates of ACP are low. Seventeen participants took part comprising family members, old age psychiatrists and policy makers. Thirty‐two items reached consensus. The panel agreed on 11 different areas for discussion. They concurred that ACP was best addressed after the person has come to terms with the diagnosis when the individual feels ready to do so. There was a consensus view that the process should be couched in terms of 'certain possibilities'. Consensus items emphasised personal choice and autonomy, while also prioritising the need to discuss financial aspects and to include spouses. There was no consensus that professionals should be involved, although the panel viewed them as carrying some responsibility for low uptake. It is suggested that ACP should include general discussion of values as well as coverage of specific points. Professionals need to offer discussion and information on ACP, but also make clear that the patient has the right to choose whether to pursue ACP or not.